THE EFFECT OF BLACK CUMIN (Nigella sativa) SUPPLEMENTATION THROUGH DRINKING WATER ON THE HISTOLOGY OF SMALL INTESTINE AND LARGE INTESTINE OF BROILER CHICKENS - Hartono, Madi; Santosa, Purnama Edy; Ermawati, Ratna; Sirat, Muhammad Mirandy Pratama (Universitas Syiah Kuala, 2021)
This study aimed to determine the effect of black cumin (Nigella sativa) supplementation through drinking water on the histology of broiler chickens small intestine and large intestine. The research was conducted from April-September 2020 in a cage facility of the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. This research used a completely randomized design with four treatment groups and three replications (five broilers per replication) with a total of 60 male broilers. The treatments were drinking water without Black Cumin (P0, control); drinking water with Black Cumin 36 mg/kg BW/day (P1); 72 mg/kg BW/day (P2); and 144 mg/kg BW/day (P3). Three broilers from each group were randomly necropsied at 31 days old, and samples of the small intestine (duodenum, jejunum, and ileum) and large intestine were fixed with 10% formalin solution and sent to the Lampung Disease Investigation Center for histological preparations. The observation of preparations was carried out microscopically using the Leica DM500 Binocular Microscope to accurately calculate various parameter sizes. The results were analyzed statistically with one way Analysis of Variance at significant level 5% and if proven significant, then a Tukey test was conducted. The results of this study were that the supplementation of black cumin 72 mg/kg BW/day through drinking water could significantly increase (P0.05) 1) the average sizes of villi height and villi area of small intestine (duodenum, jejunum, ileum) and large intestine (colon) of broiler chickens; 2) the average sizes of basal villi width, villi apex width, and gland diameter of broiler duodenum; and 3) the average size of apex villi width of broiler colon. The conclusion of this study was the supplementation of black cumin at dose of 72 mg/kg BW/day through drinking water could increase the histological sizes of the small intestine and large intestine of broilers.